Projeto de um sistema para reabilitação de membros inferiores - Oberdörfer, Maurício (2020)
People with motor problems find it difficult to perform simple tasks, such as locomotion, food and hygiene, becoming dependent on help to perform them. In most cases, it is necessary to use physiotherapy techniques to assist in rehabilitation. The use of technology makes the physical rehabilitation processes of patients more effective. An example of this is the Continuous Passive Motion (CPM) equipment, which is used in the first phase of limb rehabilitation by the continuous controlled movement of the joint, a determining factor, according to the literature, for the increase of motor ability and improvement in the development of functional activities. The concept of continuous passive movement appears as a counterpoint to that of immobilization in orthopedic problems. It aims to rehabilitate the joint and the tissues, through movement, stimulates the metabolism of the cells of the cartilaginous tissue. The objective of this work is to design and build a CPM-type prototype indicated for the rehabilitation of lower limbs. In this project, a product development methodology was employed until the final variant of the lower limb rehabilitation system was obtained. The preliminary design and details were developed to validate the concept, and the prototype was manufactured to test its operation.